Wireless multi-access environments and quality of service provisioning solutions and application - Muntean, Gabriel-Miro, 1972-; Trestian, Ramona, 1983- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book serves as a vital resource for practitioners to learn about the latest research and methodology within the field of wireless technology, covering important aspects of emerging technologies in the heterogeneous next generation network environment with a focus on wireless communications and their quality"--Provided by publisher.